MANAGER IN EARLY CHILDHOOD EDUCATION: ANTAGONIST OR COOPERATOR OF TEACHING WORK (REMUNOM, 2025)
School management in early childhood education seeks the integral development of children, focusing on their physical, emotional, social and cognitive development. However, the role of the school manager is still often associated with bureaucratic practices and distanced from the daily pedagogical reality. This scenario proved to be challenging when analyzing the role of the manager in articulating with teachers and in conducting pedagogical projects in early childhood education. The topic in question was limited to the analysis of the role of the school manager in this segment, questioning whether his/her stance is cooperative or antagonistic in relation to teaching practices. This research shows the ͏importance of active leadership, ͏sensitive to the particularities of childhood and committed to the work of teachers. It ends with the idea that overcoming the difficulties ͏faced in early childhood education depends on school management ͏promoting dialogue, active listening, and ͏engagement with the collective during the practical and meaningful construction for the development of children.